Against all odds: anti-IgE for intrinsic asthma?. Issue 1 (24th May 2013) - Lommatzsch, Marek; Korn, Stephanie; Buhl, Roland; Virchow, Johann Christian
Abstract : For many years, pathogenetic concepts and the results of clinical trials supported the view that anti-IgE treatment is specifically effective in allergic asthma. However, there is now growing clinical and mechanistic evidence suggesting that treatment with the anti-IgE antibody omalizumab can be effective in patients with intrinsic asthma. Therefore, large and well-controlled clinical trials with anti-IgE are urgently warranted in patients with intrinsic asthma. In addition, there is a need to find new biomarkers which can identify patients with asthma who respond to anti-IgE treatment.